Pencarian Rute Terbaik pada Obyek Wisata di Kabupaten Banyumas Menggunakan Algoritma Genetika Metode TSP - Imam Tahyudin; Ika Susanti (JUITA : Jurnal Informatika, 2015)
There are many wonderful tourist attractions in Banyumas. Based on data which are obtained, its number are 25 locations while in this research focus on 11 objects as experiment. The purpose of this study was to determine the best path that connects the eleventh object using Genetic Algorithms especially TSP method. Based on the results are the best path length is 0.878 units of Cartesian with a population size is 25 and the probability of mutations is 0,005. The sequence paths are Purwokerto square, Andang pangrenan Parks, Baturraden, Dreamland Waterboom Ajibarang, Cipendok waterfall, educational tours of STMIK AMIKOM Purwokerto, Depo Bay Sokaraja, Goa Maria Kaliori, Museum of General Sudirman, BRI Museum, and Bale Kemambang